Impact of Modality and Intensity of Early Exercise Training on Ventricular Remodeling after Myocardial Infarction - Batista, Diego Fernando [UNESP]; Polegato, Bertha Furlan [UNESP]; Da Silva, Renata Candido [UNESP]; Claro, Renan Turini [UNESP]; Azevedo, Paula Shmidt [UNESP]; Fernandes, Ana Angélica [UNESP]; Okoshi, Katashi [UNESP]; De Paiva, Sergio Alberto Rupp [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Zornorff, Leonardo Antônio Mamede [UNESP] (Hindawi, 2020)
The objective of this study was to analyze the impact of different modalities and intensities of exercise training on cardiac remodeling started early after experimental myocardial infarction (MI). Male Wistar rats, weighing 200-250 g, were subjected to experimental MI. After 5 days, the animals were allocated into three experimental groups and observed for three months: S (sedentary control animals), C (animals subjected to continuous low-intensity training), and HIT (animals subjected to high-intensity interval training). Low-intensity exercise training was performed at a treadmill speed corresponding to 40% VO2 max, which was kept unchanged throughout the entire session (i.e., continuous low-intensity training). High-intensity interval training was performed in such a way that rats run during 3 min at 60% VO2 max, followed by 4-minute intervals at 85% VO2 max (i.e., high-intensity interval training). After the follow-up period, we studied hypertrophy and ventricular geometry, functional alterations in vivo and in vitro, oxidative stress, apoptosis, and cardiac energetic metabolism. Our data showed that both high-intensity interval and continuous low-intensity modalities improved cardiac energetic metabolism variables in comparison with sedentary infarcted animals. In addition, high-intensity interval training decreased cardiac oxidative stress, associated with improved diastolic function. On the other hand, the continuous low-intensity group showed impairment of cardiac function. Therefore, altogether, our data suggest that high-intensity interval training could be the best modality for early physical exercise after MI and should be better studied in this clinical scenario.